Identify the Disciplinary Attitude of Learning Physics in High School Students - Roro Hoyi; Liza Liza (Journal Evaluation in Education (JEE), 2021)
Purpose of Study: The purpose of this study was to determine the disciplinary attitude of students in learning physics. Methodology: The sample used in this study were 31 students, taken from 1 class, namely XI MIPA 3. This type of research is survey research and the instrument used is an attitude questionnaire. The data analysis in this study used descriptive statistics. Finding: The results obtained showed that the discipline attitude of learning physics students was dominant good, namely 74.2% 23 students from 31 students. From the disciplinary attitude itself, the fact is that the quality of student learning is better and also students who have a high disciplinary attitude in learning physics must have different behavior and patterns of thought. Novelty this Research: The general attitude towards reading is an indicator that shows how positive students think about various things about reading in general. This indicator will be measured by researchers to determine whether or not reading is good for students.